Electrospinning application on fabrication of PMMA nanofibers membranes for electrochemical sensors - Postolache, O.; Macovei, S.; Trandabat, A.; Hogas, I. (International Conference and Exposition on Electrical And Power Engineering, EPE 2018, 2018)
The present paper focus on research carried out to optimize manufacturing of the electrochemical sensors electrodes based on nanostructured hybrid composite interface at nano and micro-scale. To obtain the nanofibers the electrospinning method was considered and several experimental research were carried out to extract the effect of solution parameters and electrospinning parameters on the characteristics of nanofibers membranes to be used later as support for ceramic materials that are employed for the construction of ceramic nanotubes. The characteristics of the obtained nanofibers membranes were analyzed using 1000x microscope. Regarding the experimental study different PMMA solution characterized by wt=5% and wt= 10% concentrations, were used for different high voltage values applied between needle and collector drum and different distances between the needle and metallic support surface. Different experimental setups were carried out followed by analysis and comparisons between the nanofibers obtained by electrospinning and also about ZnO deposition on the nanofibers level.